Trio sequencing in pediatric cancer and clinical implications - Kuhlen, Michaela (EMBO Mol Med, 2018)
In pediatric cancer, we advocate for trio sequencing of the child and its parents. This method can have substantial implications for cancer prevention in parents and siblings and even in more distant family members. It does not only help to identify a putative classical cancer predisposition syndrome in the index patient, but also detects the combinatorial effect of two independent risk variants in the same signaling pathway. This type of inheritance pattern could contribute to explaining the early occurrence of cancer in children and young adults and thereby inform early diagnosis, screening and preventive measures.